Purificação e caracterização de proteínas de venenos de serpentes que interferem na cascata de coagulação sanguínea - Oliveira, Daniella Gorete Lourenço de [UNESP] (2006)
Toxins isolated from vemos have been used as molecular tools to understand many physiological processes. The enzymes isolated from the venoms of Crotalus and Bothrops species interfere with the control and balance of the hemostatic system (PEREZ et al., 1996) and thus, the determination of their structures is potentially very important. These enzymes are serine proteinases that are similar to tyrpsin in their specificity but are generally referred to as thrombin-like enzymes due to their ability to cleave fibrinogen. The principal aim of this project was to isolate and characterize snake venom poteins that inetefere with the control and regulation of the hemostatic system in quantities and purity required for structural studies. Gel filtration, ion-exchange and HPLC chromatographic techniques were used to isolate convulxin, crotoxin, giroxin and crotamine, the principle components from the venoms of Crotalus durissus collineatus and Crotalus durissus terrificus and the serine and metalo proteinases from the venom of Bothrops jararaca. The purity of the samples was evaluated by SDS-PAGE and the specific activity of the samples was determined. Crystallization experiments were then carried out.